Respostas reprodutivas de fêmeas de jundiá (Rhamdia quelen) alimentadas com diferentes fontes protéicas e lipídicas - Parra, Jorge Erick Garcia (2007)
The aim of the work was to evaluate the effect of different protein and lipid sources of animal and vegetable origin on the reproductive performance of black catfish Rhamdia quelen females. Three experiments were accomplished with duration of 90 days each, divided in three phases: Phase I, Reproducers feeding; phase II, Induced reproduction and eggs and larvae incubation; phase III, Larvae culture. Fifteen females of black catfish (around 700g) were used for experiments 1 and 2, and 500g for experiment 3. The females were distributed in three net cages of 1m³, 5 fish (4 females for induction and 1 for oocyte collection). The fish were fed for ten weeks using three diets as treatments: experiment 1, meat and bone meal and soybean meal (CS), fish meal and soybean meal (PS) and yeast and soybean meal (LS); For experiment 2, the effect of substitution of the meat and bone meal for the soybean meal in increasing levels was evaluated (0%, 35%, 70%), that were treatments CS 0, CS 35 and CS 70; In experiment 3, pork fat (BP), sunflower oil (OG) and Canola oil (OC). After induced spawning, samples of ten eggs were collected at the moment of the fishes spawning, at 3, 9, 12, 18 and 24 hours. Also samples of ten larvae were collected, at the moment of the eclosion, at 12, 24, 36 and 48 hours. Three samples of larvae of each incubator in the density of 30 larvae/l, were collected and fed during 14 days. Changeable zoogenic were esteem for phases I and III and reproductive for phase II. In experiment 1, females fed with the diet of treatment LS, had shown minor profit in weight, the eggs had equally minor weight. For the embryonic evelopment treatments, CS and PS were superior to treatment LS in the variable (DSV). In the larval development in the incubators, treatment CS showed better performance for the variable (CT). For the experiment 2, females fed with diets CS 70, had not answered the spawning of fishes. The embryonic development, larval vitelline and larvae were superior in treatment CS 0 for the variable (DO and AO), (CT and AT), (CT, CP, Area, SOB) respectively. In experiment 3, the larvae development in the incubators, treatment BP was minor that treatment OG in the variable (CT), equally treatment BP was minor that treatments OG and OC for the variable (DSV). For the larval development until the 14 days treatment OC was greater that treatment BP for the variable (CT and CP). We can conclude that the use of Meat and Bone meal and Soybean meal as protein sources are presented as good option in the feeding of reproductive females of black catfish. The pork fat is so good as sunflower and canola oils as lipid sources for reproductive females and they provide good development of the embryo and jundiá s larvae